2006
DOI: 10.1111/j.1460-9568.2006.04621.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous opioids upregulate brain‐derived neurotrophic factor mRNA through δ‐ and µ‐opioid receptors independent of antidepressant‐like effects

Abstract: Systemic administration of δ-opioid receptor (DOR) agonists decreases immobility in the forced swim test (FST) and increases brain-derived neurotrophic factor (BDNF) mRNA expression in rats, indicating that DOR agonists may have antidepressant-like effects. The aim of this study was to investigate the effects of central administration of endogenous opioid peptides on behavior in the FST and on brain BDNF mRNA expression in rats. Effects of endogenous opioids were compared with those produced by intracerebroven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 56 publications
(82 reference statements)
1
53
0
Order By: Relevance
“…The conflicting results might be explained by several methodological differences, of which the shorter treatment period might be the most critical factor (Boehm et al 2006;Shishinka et al 2007). A recent study reports the effects of enkephalins on behavior and BDNF expression in the hippocampus (Zhang et al 2006). In our study, we also determined a robust increase in Bdnf expression in the hippocampus of paroxetine-treated DBA/2 mice.…”
Section: Paroxetine Enhances Preproenkephalin 1 (Penk1) Expressionmentioning
confidence: 64%
“…The conflicting results might be explained by several methodological differences, of which the shorter treatment period might be the most critical factor (Boehm et al 2006;Shishinka et al 2007). A recent study reports the effects of enkephalins on behavior and BDNF expression in the hippocampus (Zhang et al 2006). In our study, we also determined a robust increase in Bdnf expression in the hippocampus of paroxetine-treated DBA/2 mice.…”
Section: Paroxetine Enhances Preproenkephalin 1 (Penk1) Expressionmentioning
confidence: 64%
“…Enhancement in synaptic strength as well synaptic reorganization after HFS at this pathway has been found to be NMDA receptor-independent and dependent on the activation of opioid receptors, which are expressed in high concentrations at this area (Derrick et al, 1991;Escobar et al, 1997). It has also been reported that opioid receptor activation increases BDNF mRNA in hippocampal neurons (Zhang et al, 2006). Some of BDNF's principal targets are the activation of adenylyl cyclase that activates protein kinase A (PKA) and metabotropic glutamate receptors (mGluR), which have been reported to be essential for hippocampal mossy fiber LTP (Henze et al, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, centrally administered endomorphin-1 and -2 were shown to increase BDNF mRNA expressions in hippocampus and amygdala (Zhang et al, 2006). BDNF participates in synaptic plasticity mechanisms, such as long-term potentiation, learning, and memory (Huang and Reichardt, 2001;Malcangio and Lessmann, 2003).…”
Section: A Biological Effects Of Endomorphinsmentioning
confidence: 99%
“…Zhang et al (2006) examined the effects of i.c.v. administered endomorphins, at doses active in other behavioral studies (30 and 90 nmol/animal, i.e., ϳ20 and 50 g/animal), on animal behavior in the FST and on brain-derived neurotrophic factor (BDNF) gene expression in rats.…”
Section: A Biological Effects Of Endomorphinsmentioning
confidence: 99%
See 1 more Smart Citation